CHATIME’S DIGITAL MARKETING, PROMOTION, AND EWOM IMPACT ON THE ROLE OF PURCHASING INTEREST AS A MEDIATOR IN IMPROVING PURCHASE DECISION - Muhamad Farid Mahmud; Lies Handrijaningsih; Salman Alfarisi (Universitas Gunadarma, 2025)
Encouraging consumer purchasing interest is an important phase in the marketing process because product competition is tightening and providing easy access to information and excellent services, particularly in the ready-to-drink beverage market. The goal of this study is to investigate and evaluate the role of purchasing interest in mediating the impact of digital marketing, promotion, and electronic word-of-mouth on Chatime purchasing decisions in Pondok Cina, Depok. Primary data from 210 respondent questionnaires was analyzed quantitatively. SmartPLS performs multivariate analysis using the Structural Equation Model approach. In addition to demonstrating the mediating role of purchasing interest and the importance of marketing using digital channels, promotion, and electronic word of mouth in driving purchasing decisions; the study's findings explain strategies for driving purchasing decisions in increasingly competitive beverage shops.